Deteksi Bakteri Clavibacter michiganensis subsp. michiganensis pada Benih Tomat Komersial yang Beredar di Indonesia - Aswaldi Anwar; Satriyas Ilyas; Sudarsono Sudarsono (Universitas Gadjah Mada, 2004)
The existence of Clavibacter michiganensis subsp. michiganensis (Cmm), the pathogen causing bacterial canker, on 22 lots of tomato seeds distributed commercially in Indonesia was evaluated. Isolation of suspected Cmm colonies were conducted by agar dilution plating on semiselective SCM medium followed by confirmation of colony identity on YDC medium. Identity of suspected Cmm colony was confirmed using IF test, pathogenicity test on tomato seedlings, hypersensitivity test on leaf of Mirabilis jalapa and Nicotiana tabacum, ELISA, and Cmm specific DNA amplification by PCR. After seed extraction and evaluation of the extract on semi-selective SCM medium and confirmastion by IF test, at least six tomato seed lots were contaminated with Cmm. After more confirmation using pathogenicity and hypersensitivity test, ELISA, and PCR amplification, at least three seed lots were confirmed possitively to carry Cmm.